Plant-Produced Receptor-Binding Domain of SARS-CoV-2 Elicits Potent Neutralizing Responses in Mice and Non-human Primates - Siriwattananon, Konlavat; Manopwisedjaroen, Suwimon; Shanmugaraj, Balamurugan; Rattanapisit, Kaewta; Phumiamorn, Supaporn; Sapsutthipas, Sompong; Trisiriwanich, Sakalin; Prompetchara, Eakachai; Ketloy, Chutitorn; Buranapraditkun, Supranee; Wijagkanalan, Wassana; Tharakhet, Kittipan; et al. (Frontiers in Plant Science, 2021)
The emergence of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected global public health and economy. Despite the substantial efforts, only few vaccines are currently approved and some are in the different stages of clinical trials. As the disease rapidly spreads, an affordable and effective vaccine is urgently needed. In this study, we investigated the immunogenicity of plant-produced receptor-binding domain (RBD) of SARS-CoV-2 in order to use as a subunit vaccine. In this regard, RBD of SARS-CoV-2 was fused with Fc fragment of human IgG1 and transiently expressed in Nicotiana benthamiana by agroinfiltration. The plant-produced RBD-Fc fusion protein was purified from the crude extract by using protein A affinity column chromatography. Two intramuscular administration of plant-produced RBD-Fc protein formulated with alum as an adjuvant have elicited high neutralization titers in immunized mice and cynomolgus monkeys. Further it has induced a mixed Th1/Th2 immune responses and vaccine-specific T-lymphocyte responses which was confirmed by interferon-gamma (IFN-γ) enzyme-linked immunospot assay. Altogether, our results demonstrated that the plant-produced SARS-CoV-2 RBD has the potential to be used as an effective vaccine candidate against SARS-CoV-2. To our knowledge, this is the first report demonstrating the immunogenicity of plant-produced SARS-CoV-2 RBD protein in mice and non-human primates.